Photooxidation and Virus Inactivation using TiO2(P25)–SiO2 Coated PET Film - Chaowat Autthanit; Supachai Jadsadajerm; Oswaldo Núñez; Purim Kusonsakul; Jittima Amie Luckanagul; Visarut Buranasudja; Bunjerd Jongsomjit; Supareak Praserthdam; Piyasan Praserthdam (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
This study chemically modified PET film surface with P25 using silicate as a binder. Different P25–binder ratios were optimized for the catalyst performance. The modified samples were analyzed by scanning electron microscopy-energy-dispersive X-ray spectroscopy and Fourier transform infrared spectroscopy. Diffuse reflectance UV-vis spectra revealed significant reductions in the band gaps of the P25 solid precursor (3.20 eV) and the surface-modified PET–1.0Si–P25 (2.77 eV) with visible light. Accordingly, under visible light conditions, catalyst activity on the film will occur. Additionally, the film’s performance was evaluated using methylene blue (MB) degradation. Pseudo-first-order-rate constants (min−1), conversion percentages, and rates (µg.mL−1.gcat−1.h−1) were determined. The coated films were evaluated for viral Phi–X 174 inactivation and tested with fluorescence and UV-C light illumination, then log (N/N0) versus t plots (N = [virus] in plaque-forming units [PFUs]/mL) were obtained. The presence of nanosilica in PET showed a high adsorption ability in both MB and Phi–X 174, whereas the best performances with fluorescent light were obtained from PET–1.0Si–P25 and PET–P25–1.0Si–SiO2 equally. A 0.2-log virus reduction was obtained after 3 h at a rate of 4×106 PFU.mL−1.gcat−1.min−1. Additionally, the use of this film for preventing transmission by direct contact with surfaces and via indoor air was considered. Using UV light, the PET–1.0Si–P25 and PET–1.0Si–P25–SiO2 samples produced a 2.5-log inactivation after 6.5 min at a rate of 9.6×106 and 8.9×106 PFU.mL−1.gcat−1.min−1, respectively. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).